Wczesnochrześcijański zespół kościelno-grobowy w Achc w Armenii. Analiza architektoniczno-ikonograficzna - Próchniak, Daniel (Vox Patrum, 2008)
The small village of Akhts at the Southern slopes of Mount Aragats in Armenia preserves the ruins of an extremely interesting temple-sepulchral complex. Its oldest part is the mausoleum of Armenian rulers, mentioned in several historical texts, e.g. in Buzandaran Patmutiwnk (IV 24), or by Moses Khorenats’i (III 27). The complex was erected no later than by the sixth decade of the 4th century; after the year 364, a three-aisled basilica was added to the mausoleum. Both the architecture and the relief decoration have been analysed on numerous occasions (e.g. A. Khatchatrian, or F. Gandolfo, among others).The aspect which still requires a closer analysis, however, is the interpretation of one of the scenes carved on the stone slab closing the Southern arcosolium of the mausoleum (Fig. 10 and 12). The figure of a man fighting a wild boar has been traditionally interpreted as a representation of a hunter or, in the astral-mythic context, as one of the legendary ancestors of the Armenians, Ara the Beautiful (L.A. Dumovo) or Haik-Orion (B.N. Arakeljan). The scene, however, can be also interpreted as a symbolic allusion to the Chris- tianising of Armenia at the beginning of the 4th century. Both the representation of the wild boar, and the figure of the hunter/Ara/Haik can be seen as the same person, king Tiridates III, in two stages of his life: before and after Christianisation. The king’s story has been vividly recounted by Agathangelos. Initially, the ruler was a zealous persecutor of Christians. As a punishment, he was afflicted with lycantrophy: he believed he had been tumed into a wild boar. The only way to recover was to adopt Christianity, which the king did, turning this time into an eąually zealous persecutor of pagans. Therefore, the stone slab in Akhts may represent Tiridates- the Christian fighting his earlier, pagan avatar.